Dyslipidemia in ART-naive HIV-infected persons in Nigeria-implications for care (2014)
Aims: This study aimed to describe the prevalence and pattern of lipid abnormalities among antiretroviral therapy (ART)- naive HIV patients, understand if there is any relationship to virologic and immunologic status, and discuss the implications for care. Methods: This was a cross-sectional study in which baseline demographic, clinical, and laboratory data of all ART-naive HIV-infected individuals recruited into the adult ARV clinic, University College Hospital, Ibadan, between January and December 2006, were analyzed. Results: In total, 1316 ART-naive HIV-infected persons were recruited in the period. Females subjects and participants aged 35 years accounted for 67.1% and 57.7% of all participants, respectively. At least 1 abnormal lipid fraction was seen in 73.3% of participants. It was observed that in 11.5% participants the total cholesterol (TC) was ≥5.2 mmol/L, in 2.7% the low-density lipoprotein cholesterol (LDL)-C was >4.1 mmol/L in 56.5% the high-density lipoprotein cholesterol (HDL)-C was <1.0 mmol/L, and in 27.6% the triglyceride (TG) was >1.7 mmol/L. The TC, LDL-C, and HDL-C were all significantly positively correlated with CD4 counts and negatively correlated with viral load. On the contrary, the TG levels were negatively correlated with CD4 counts and positively correlated with viral load. Multivariate linear analysis showed a significant relationship between all the lipid parameters and viral load. CD4 counts were only significantly associated with TC. Conclusions: A significant burden of dyslipidemia exists among ART-naive HIV-infected persons. Low HDL-C was the most frequently observed abnormality. The abnormalities related more with viral load levels than with CD4 counts. Dyslipidemia screening should be done in ART-naive HIV-infected persons. Simple healthy lifestyle changes should be emphasized, with other care given to those with the disorder.